Knowledge Organization from an Indigenous Perspective: The Mashantucket Pequot Thesaurus of American Indian Terminology Project - Littletree, Sandra; Metoyer, Cheryl A. (Cataloging & classification quarterly, 2015)
Native Americans create, preserve, and organize knowledge within the context of community, thereby ensuring the inclusion of Native American philosophies. Historically, mainstream cataloging and classification systems have not adequately represented this knowledge. The Mashantucket Pequot Thesaurus of American Indian Terminology was designed to incorporate an Indigenous perspective into mainstream controlled vocabularies. Using story as pedagogy, this article examines the conceptual foundations, theoretical framework, and application of the Thesaurus to a museum setting.